Advanced multi-criteria decision making for addressing complex sustainability issues - Chatterjee, Prasenjit 1982-; Yazdani, Morteza; Chakraborty, Shankar 1962-; Panchal, Dilbagh (IGI Global, 2020)
"This book examines different types of decision-making modeling in addressing complex sustainability issues in the areas of economics, business, manufacturing, management, and mechanical engineering"--
Description based on title screen (IGI Global, viewed 04/16/2019)
Keywords: Sustainable engineering; Green products; Sustainable development; Multiple criteria decision making